Anti-NMDA receptor encephalitis concomitant with myelin oligodendrocyte glycoprotein antibody diseases: A retrospective observational study. Issue 31 (31st July 2020) - Du, Li; Wang, Huabing; Zhou, Heng; Chang, Haoxiao; Wei, Yuzhen; Cong, Hengri; Xu, Wangshu; Ma, Yuetao; Song, Tian; Zhang, Xinghu; Yin, Linlin
Abstract : Abstract: Anti-N-methyl-D-aspartate receptor encephalitis (NMDARe) can coexist with myelin oligodendrocyte glycoprotein antibody (MOG-ab) disease. To characterize MOG-ab disease during NMDARe, we analyzed all the patients with MOG-ab disease and NMDARe from our hospital from December 2018 to December 2019 and data from a systematical review of previously published reports. Details of the patients identified were summarized and literature was reviewed. Four of thirty (14.2%) patients with anti-NMDARe had overlapping MOG-ab disease in our department. Analyze together with previously reported cases. Thirty-two NMDARe patients had overlapping MOG-ab disease. The onset age ranged from 3 to 48 years. Twenty-four patients (74%) developed abnormal behavior or cognitive dysfunction during the episodes of anti-NMDARe. None of these patients had tumors. 84% (27/32) patients received high doses of steroids as first-line immunotherapy and 28% (9/32) received mycophenolate mofetil (MMF) to prevent relapse. Twenty-six of twenty-seven (96%) had a good outcome. Steroids are the most common first-line immunotherapies in NMDARe overlapping MOG-ab disease. Most of the NMDARe patients overlapping MOG-ab disease have a good prognosis.